2020
DOI: 10.1021/acscatal.0c01842
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Enantioselective Reductive Cross-Coupling Reactions

Abstract: Nickel-catalyzed reductive cross-coupling reactions have emerged as powerful methods to join two electrophiles. These reactions have proven particularly useful for the coupling of sec-alkyl electrophiles to form stereogenic centers; however, the development of enantioselective variants remains challenging. In this Perspective, we summarize the progress that has been made toward Ni-catalyzed enantioselective reductive cross-coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
170
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(187 citation statements)
references
References 114 publications
4
170
0
13
Order By: Relevance
“…Merging photoredox and Cu catalysis offers new avenues for stereoselective transformations by providing a dual catalytic manifold in which efficient radical generation and stereocontrolled product formation generally occur in two separate cycles [3d, 30] …”
Section: Enantioselective Transformationsmentioning
confidence: 99%
“…Merging photoredox and Cu catalysis offers new avenues for stereoselective transformations by providing a dual catalytic manifold in which efficient radical generation and stereocontrolled product formation generally occur in two separate cycles [3d, 30] …”
Section: Enantioselective Transformationsmentioning
confidence: 99%
“…Control experiments confirmed that all components (Ni, ligand, current, additive) were essential for the reaction outcome. Although not specifically discussed in the paper, the cross-coupling has been considered to follow a sequential reduction mechanism [118,119] taking into account results that proved inconsistent with a radical chain mechanism for the non-electrochemically-driven variant of the reaction [120]. In the sequential reduction pathway, a Ni 0 complex would be generated from electroreduction of the Ni II precursor, and the C(sp 2 ) coupling partner (the alkenyl bromide) would undergo oxidative addition with this Ni 0 species.…”
Section: Cross-electrophile Couplingsmentioning
confidence: 99%
“…Die Kombination von Photoredox‐ und Cu‐Katalyse bietet neue Möglichkeiten für stereoselektive Transformationen, wobei die effiziente Generierung von Radikalen sowie die stereokontrollierte Produktbildung generell in zwei separaten Katalysezyklen erfolgen [3d, 30] …”
Section: Enantioselektive Transformationenunclassified
“…2014 hat unsere Gruppe die erste duale Photoredox/Ni-Katalyse zur Konstruktion von C(sp 2 )-C(sp 3 )-Bindungen unter milden Reaktionsbedingungen beschrieben, welche mit zahlreichen funktionellen Gruppen kompatibel ist (Schema 1A). [1a] In diesem Bericht wurde gezeigt, dass Benzyltrifluoroborate (E 1/2 =+1.10 Vg egen SCE) oxidativ fragmentieren und dabei Radikale bilden, welche in Ni-katalysierten Kreuzkupplungen eingesetzt werden kçnnen.…”
Section: Ni-katalysierte Enantioselektive Transformationenunclassified
See 1 more Smart Citation